1999
DOI: 10.1038/sj.bjc.6690408
|View full text |Cite
|
Sign up to set email alerts
|

Loss of functional pRB is not a ubiquitous feature of B-cell malignancies

Abstract: Summary Human cancers frequently sustain genetic mutations that alter the function of their G1 cell cycle control check point. These include changes to the retinoblastoma gene and to the genes that regulate its phosphorylation, such as the cyclin-dependent kinase inhibitor p16 INK4a . Altered expression of retinoblastoma protein (pRb) is associated with non-Hodgkin's lymphoma, particularly centroblastic and Burkitt's lymphomas. pRb is expressed in normal B-cells and its regulatory phosphorylation pathway is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…These results might suggest that the pRb pathway is inactivated in a fraction of BL lines and tumors. Other groups have shown, however, that pRb appears functional and normally expressed and phosphorylated in BL [81]. Supporting this notion, we found that pRb readily interacts with E2F family members in different BL cell lines regardless of EBV status [82].…”
Section: Alterations In Sporadic Burkitt's Lymphomasupporting
confidence: 69%
“…These results might suggest that the pRb pathway is inactivated in a fraction of BL lines and tumors. Other groups have shown, however, that pRb appears functional and normally expressed and phosphorylated in BL [81]. Supporting this notion, we found that pRb readily interacts with E2F family members in different BL cell lines regardless of EBV status [82].…”
Section: Alterations In Sporadic Burkitt's Lymphomasupporting
confidence: 69%
“…In this study, RB1 protein expression was identified in most C-ALCL, lymphomatoid papulosis, and transformed MF cases, but not in inflammatory dermatosis. Previous IHC studies have also revealed the presence of RB1 protein expression in tumour cells in relapsing Hodgkin's disease (Amini et al, 2002), adult T-cell leukemia/lymphoma (Nakayama et al, 2000), B-cell lymphomas (Sinclair and Frost 1999), and MALT lymphoma (Stefanaki et al, 1998). The IF8 antibody mainly recognizes the phosphorylated form of RB1 protein, which tends to accumulate in highly proliferating dividing cells such as human colorectal cancer (www.scbt.com), whereas in inflammatory dermatosis such as psoriasis and lichen planus the hypophosphorylated RB1 protein is mainly expressed and therefore not detected by IHC with IF8 antibody.…”
Section: Discussionmentioning
confidence: 96%
“…2 All subtypes of BL are characterized by translocation of genetic material between the long arm of chromosome 8 (8q24) and the immunoglobulin heavy chain region on chromosome 14, resulting in t (8;14). The translocation may infrequently occur between 8q24 and the kappa light chain locus on chromosome 2 (t (2,8)) or between 8q24 and the lambda light chain locus on chromosome 22 (t (8,22)). Regardless of which of these translocations occurs, the result is deregulation of the oncogene c-myc.…”
Section: Introductionmentioning
confidence: 99%
“…8 The retinoblastoma family is composed of 3 members, pRb/p105, p107, and pRb2/p130. 9 Many of the sequence similarities among these genes reside in a homologous functional domain known as the pocket region.…”
Section: Introductionmentioning
confidence: 99%